Public childcare, labor market outcomes of caregivers, and child development: Experimental evidence from Brazil - Orazio P. Attanasio; Ricardo Paes De Barros; Pedro Carneiro; David K. Evans; Lycia Lima; Pedro Olinto; Norbert Rüdiger Schady (Centre for Microdata Methods and Practice (cemmap), 2022)
This study examines the impact of publicly provided daycare for children aged 0-3 on outcomes of children and their caregivers over the course of seven years after enrollment into daycare. At the end of 2007, the city of Rio de Janeiro in Brazil used a lottery to assign children to limited public daycare openings. Winning the lottery translated to a 34 percent increase in time in daycare during a child's first four years of life. This allowed caregivers more time to work, resulting in higher incomes for beneficiary households in the first year of daycare attendance and 4 years later (but not after 7 years, by which time all children were eligible for universal schooling). The rise in labor force participation is driven primarily by grandparents and by adolescent siblings residing in the same household as (and possibly caring for) the child, and not by parents, most of whom were already working. Beneficiary children saw sustained gains in height-for-age and weight-for-age, due to better nutritional intake at school and at home. Gains in beneficiary children's cognitive development were observed 4 years after enrolment but not later.
Keywords: I21; I28; J22; O15; 330; Early child development; childcare; Brazil; Kinderbetreuung; Wirkungsanalyse; Kinder; Gesundheit; Kognition; Haushaltseinkommen; Arbeitsangebot; Rio de Janeiro; Brasilien